Carbon Papers from Tall Goldenrod Cellulose Fibers and Carbon Nanotubes for Application as Electromagnetic Interference Shielding Materials - Jihyun Park; Lee Ku Kwac; Hong Gun Kim; Hye Kyoung Shin (Molecules, 2022)
To transform tall goldenrods, which are invasive alien plant that destroy the ecosystem of South Korea, into useful materials, cellulose fibers isolated from tall goldenrods are applied as EMI shielding materials in this study. The obtained cellulose fibers were blended with CNTs, which were used as additives, to improve the electrical conductivity. TGCF/CNT papers prepared using a facile paper manufacturing process with various weight percent ratios and thickness were carbonized at high temperatures and investigated as EMI shielding materials. The increase in the carbonization temperature, thickness, and CNT content enhanced the electrical conductivity and EMI SE of TGCF/CNT carbon papers. TGCF/CNT-15 papers, with approximately 4.5 mm of thickness, carbonized at 1300 °C exhibited the highest electrical conductivity of 6.35 S cm−1, indicating an EMI SE of approximately 62 dB at 1.6 GHz of the low frequency band. Additionally, the obtained TGCF/CNT carbon papers were flexible and could be bent and wound without breaking.